Tata Kelola Keuangan Negara Madinah Dan Relevansinya Dengan Konteks Keindonesiaan - Singgih Muheramtohadi (el-Jizya : Jurnal Ekonomi Islam, 2018)
Financial Governance is one of many problems that face in Indonesia. The low of perception of Corruption Index, the budget waste, ineffeciency in budget alocation, and found so many of budget deviations. On other side, in early history of islam, financial institution have existed also known as Baitul Mal. From simpe institution form of Baitul Mal to organized institution in the age of Umar Ibn Khattab’s rule. Although Islam doesn’t teach the financial governance definitively, but there are some principles that relevant to solve thefinancial governance problems in present time. This write uses the description and analytical method, i.e to describe how to manage the financial in Baitul Mal and what values are contained that can be used in solving the financial governance’s problems. The results of this write are : 1) the govermance should restrict of expenditure budget, 2) the expenditures must be based on the real neeeds of people, especially for poor class. 3) to maximilize the revenue from large companies and cumstoms and excises. 4) to intensify the control of financial governance.